1998
DOI: 10.1089/apc.1998.12.931
|View full text |Cite
|
Sign up to set email alerts
|

A Mobile HIV Education and Testing Program: Bringing Services to Hard-to-Reach Populations

Abstract: Few programs exist that offer a range of human immunodeficiency virus (HIV) services to multiple populations (i.e., substance abusers, individuals on probation, sex workers and their clients, court-mandated perpetrators of domestic violence) in multiple settings (i.e., courts, methadone maintenance clinics, residential and outpatient substance abuse treatment programs). The purpose of this article is to describe a model mobile HIV program, highlighting its flexibility in providing services to clients who infre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…19 studies reported uptake among 41,110 participants in key populations, including 16,725 MSM [90][97], 4,681 PWID [92],[98]–[100], 81 FSW [101], 13,240 adolescents [102],[103], and 6,383 individuals from combinations of key populations. The percentage accepting HTC was 99.7% among FSW, ranged from 13.7% to 94.5% among PWID, ranged from 9.4% to 95.0% among MSM, and ranged from 33.9% to 96.6% among adolescents (Figure 10).…”
Section: Resultsmentioning
confidence: 99%
“…19 studies reported uptake among 41,110 participants in key populations, including 16,725 MSM [90][97], 4,681 PWID [92],[98]–[100], 81 FSW [101], 13,240 adolescents [102],[103], and 6,383 individuals from combinations of key populations. The percentage accepting HTC was 99.7% among FSW, ranged from 13.7% to 94.5% among PWID, ranged from 9.4% to 95.0% among MSM, and ranged from 33.9% to 96.6% among adolescents (Figure 10).…”
Section: Resultsmentioning
confidence: 99%
“…Five studies provided nontargeted testing to the general population, while the rest addressed HIV testing in one or more high‐risk populations. Eleven studies investigated HIV testing in multiple high‐risk groups . The most commonly targeted group for testing was MSM (17 studies, including two that specifically targeted BME MSM) .…”
Section: Resultsmentioning
confidence: 99%
“…HIV testing was offered at a wide range of sites. Stand‐alone HIV testing sites (14 studies ) and mobile clinics (11 studies ) were the most frequently selected sites for community testing. Several studies conducted testing in venues known to be frequented by the target population, for example drug treatment centres for IDUs or gay bars and sex on premises venues for MSM.…”
Section: Resultsmentioning
confidence: 99%
“…In order to increase the number of individuals tested for HIV, in keeping with our target of universal access, we recently developed a strategy based on bringing the healthcare package much closer to the people, through mobile HIV testing units [15], conceived to bring education and testing services to hard-to-reach population [16]. This pilot study, the first in the Central African region, clearly demonstrated the acceptability, feasibility and effectiveness of using mobile units as a tool for mass HIV testing in individuals with limited access to voluntary counseling and testing [15].…”
Section: Introductionmentioning
confidence: 99%